Мовна картина світу: проблема організації складників - Огуй, О.Д. (Мовознавство, 2013)
У статті розглядаються сфери дослідження мовної картини світу (МКС), установлюються
її характерні дефініції та ключові проблеми, у тому числі і зв’язок з концептуальною
картиною світу (ККС). На цій основі здійснюється критичний огляд їх складників (концептів
і полів) та здійснюється спроба голістично-модулярного моделювання МКС на основі
різночастиномовних лексико-семантичних полів (ЛСП). Instead of systemocentric investigation of vocabulary as lexical-semantic system of a
language a new anthropocentric paradigm is being confirmed, being based on a vague metaphor
«language picture of the world». The difficulty of its determining is caused by the juxtaposition
of superimposed polytypic categories — «world picture» (WP), «conceptual picture of the
world» (CPW) and «language picture of world» (LPW). Due to our analysis, phenomena of
reality, (re)constructed in images, lay as the basis of WP. National mentality activities,
expressed in concepts, are organized into a conceptual picture of the world (CPW). The LPW
(expressing the WP) is based upon the world of concepts (conceptual sphere) being a core of it.
The unit of LPW is not a concept (the unit of CPW), but the «lexical-semantic field» (LSF) as a
plurality of interconnected words’ paradigms. LSF as polycategoric lexical-semantic field
contains monocategoric lexical-semantic groups, making out the LSF. Due to our attempt of
formalization, LPW as a whole (universe) consists of three subclasses of interconnected
systems - MAN, surrounding REALITY and DETERMINANTS combining them. Each
subclass of LPW can be divided formally into families (a group of combined fields), types
(individual fields) and subtypes (lexical-semantic groups within their field).
The LPW (as a holistic unity) can be integrally defined as totality of linguistic experiential
modules historically reflected in the lexicon. Linguistically the language world picture reveals
itself as a systematic field organized lexicon (in the unity of tokens, their semantics and
pragmatics) for the process of mapping of cognitive and other activities of the individual in the
community. Formalized study of lexical-semantic field as polycategoric combination of
monocategoric LSGs includes phraseological units based on formal methods (V. Levitsky,
L. Bystrova & M. Kapatruk). On this basis an attempt of holistic-modular patterning of fields
has been fulfilled. Moreover, the created model of LPW, representing the lexical-semantic
system of language, can achieve relative integrity of the lexicon during its study.